Wrist kinematics during the golf drive from a bilaterally anatomical perspective - Sweeney, M.; Mills, P.; Mankad, A.; Elliot, B.; Alderson, J. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
Despite the reported importance of the wrist `un-cocking` measure in the golf swing, only anecdotal evidence exists with respect to the three dimensional or bilateral nature of wrist motion. Through the downswing such anecdotal reports suggest that good players generally maintain a fixed flexion/extension position at the left (lead) wrist but perform rapid flexion at the right (trail) wrist. To assess these anecdotal assertions, 3D wrist kinematics of 8 skilled male golfers were determined during a high velocity golf drive. Each participant used their preferred driver, with data recorded using a Vicon 3D optoreflective system operating at 400 Hz. The results support anecdotal recommendations with respect to the large extent of right wrist flexion. However, all players underwent a considerable amount of left wrist flexion, which was in contrast to common coaching recommendations.